Pengaruh Inflasi dan Tingkat Penyerapan Tenaga Kerja Terhadap Pertumbuhan Ekonomi - Mhd Fefta Julyandi (Science of Management and Students Research Journal (SMS), 2020)
This study aims at determining the effect of the inflation and the rate of labor absorption towards the economic growth in Jambi Province. The independent variables used included the inflation and the rate of labor absorption. Meanwhile, the dependent variable used was the economic growth. The data used were time series secondary data from 2000-2018 consisting of the inflation data of Jambi, labor absorption data and economic growth data in Jambi taken from the BPS in Jambi. The analytical tool used in this study was a multiple linear regression analysis, namely the analysis used to find the effect of a set of independent variables on the dependent variable. The results of this study revealed that the inflation has no significant effect towards the economic growth, and the rate of labor absorption has no significant effect towards the economic growth in Jambi. Partially, the inflation has a negative and insignificant effect towards the economic growth in Jambi. Similarly, the rate of labor absorption has a negative and insignificant effect towards the economic growth in Jambi. The effects of the inflation and the rate of labor absorption towards the economic growth in Jambi were 14.6% while the remaining was 85.4% affected by other variables.